Copepod Distribution and Diversity in Relation to Heavy Metal Profiles in the Northern Coastal Waters of the Straits of Malacca - Sa’ad, Safura (2010)
The study was undertaken to compare heavy metal contents in copepods between two different locations and to compare the biodiversity and abundance of copepods in relations to heavy metal profiles in the two areas. Samples were collected monthly for a one year period in the coastal waters off a mangrove forest in Kula Gula, Perak (between 04° 55.185‟N, 100° 27.840‟E and 04°55.006‟N, 100° 27.761‟E ) and coastal waters off an industrial area in Kuala Juru, Penang (between 05° 19.906‟N,100° 23.746‟E and 05° 19.683‟N, 100° 22.949‟E). Physico-chemical parameters in the coastal waters such as salinity, dissolved oxygen (DO), pH, temperature, conductivity and total dissolved solid (TDS) were measured in situ using Hydrolab Surveyor 4. Composite water samples for chlorophyll a, nutrients [Total Ammonium Nitrogen( TAN), Nitrite + Nitrate (NO2 + NO3) and Soluble Reactive Phosphorus (SRP)] and heavy metal analyses were collected using Nisskin water sampler, whereas, sediment samples (for heavy metal analysis) were collected using an Ekman grab. Copepod samples were collected using conical plankton net with 100 μm mesh towed vertically (from the deepest depth at each station). A total of 37 copepod species from 13 families and 16 genera were identified in both study sites. Copepod communities were dominated by small copepods from the family Paracalanidae, Oithonidae and Ectinosomatidae in both study sites. Three copepod species Parvocalanus crassirostris, Microsetella norvegica and Oithona sp were found alternately dominating copepod population in the coastal waters of the industrial area (Kuala Juru) throughout the year whereas in the coastal waters of mangrove forest (Kuala Gula), Parvocalanus crassirostris constantly dominated the total copepod populations indicating a more stable condition in the area. Higher (p<0.05) copepod density were found in Kuala Juru than Kuala Gula. However, species diversity index was significantly higher (p<0.05) in Kuala Gula compared to Kuala Juru. Pearson‟s correlation coefficient revealed that the copepod density, diversity indices and species richness were negatively (p<0.05) correlated with nutrients and heavy metal concentrations. The environmental parameters in Kuala Juru were characterized by higher concentration of nutrients (TAN, SRP) and heavy metal (Cd, Cu, Ni, Pb, Zn) contents in the seawater, sediments and copepods from those of Kuala Gula. These differences might be due to the different environmental characteristics between the two study sites. The coastal waters off Kuala Juru were influenced mainly by the industrial, agricultural and domestic effluents. On the other hand, Kuala Gula was influenced by active agricultural activities such as those in paddy fields, palm oil plantations, cage aquaculture and cockle farming. The higher heavy metal contents in water, sediments and copepods in the coastal waters off Kuala Juru than in Kuala Gula suggested that heavy metal loading from land-based sources had significant effect on the marine environment and its biota.